Ruthenium(II)-Cyclopentadienyl-Derived Complexes as New Emerging Anti-Colorectal Cancer Drugs - Catarina Teixeira-Guedes; Ana Rita Brás; Ricardo G. Teixeira; Andreia Valente; Ana Preto (MDPI AG, 2022)
Colorectal cancer (CRC) is one of the most common malignancies and one of the leading causes of cancer-related death worldwide, urging the need for new and more efficient therapeutic approaches. Ruthenium complexes have emerged as attractive alternatives to traditional platinum-based compounds in the treatment of CRC. This work aims to evaluate anti-CRC properties, as well as to identify the mechanisms of action of ruthenium complexes with the general formula [Ru(η5-C5H4R)(PPh3)(4,4'-R'-2,2'-bipyridine)][CF3SO3], where R = CH3, CHO or CH2OH and R' = H, CH3, CH2OH, or dibiotin ester. The complexes (Ru 1-7) displayed high bioactivity, as shown by low IC50 concentrations against CRC cells, namely, RKO and SW480. Four of the most promising ruthenium complexes (Ru 2, 5-7) were phenotypically characterized and were shown to inhibit cell viability by decreasing cell proliferation, inducing cell cycle arrest, and increasing apoptosis. These findings were in accordance with the inhibition of MEK/ERK and PI3K/AKT signaling pathways. Ruthenium complexes also led to a decrease in cellular clonogenic ability and cell migration, which was associated with the disruption of F-actin cytoskeleton integrity. Here, we demonstrated that ruthenium complexes, especially Ru7, have a high anticancer effect against CRC cells and are promising drugs to be used as a new therapeutical strategy for CRC treatment.